Analisis Pelayanan Kesehatan terhadap Tingkat Kepuasan Pasien di Pusat Kesehatan Masyarakat Banjaran Kota - Sutarjo, Irna Agustriana; Puspita Dewi, Lies Anggi (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024)DO - 10.51211/jak.v12i1.2822, 2024)
Community health centers are a type of health facility that coordinates primary care for individuals and groups at affordable rates. To build superior public health facilities, you must follow the norms and provisions regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 43 of 2019 concerning Community Health Centers. Patients flock to the Banjaran Kota Community Health Center, but the facility only has a rating of 3.0/5 on Google Maps and many of them remain dissatisfied with the service they receive. Therefore, the author is interested in conducting research on the influence of community health center services on patient satisfaction at the Banjaran City Community Health Center. The aim of this research is to find out whether the quality of service at the Banjaran City Community Health Center influences the level of patient satisfaction based on expectations and services obtained related to ambience elements, system factors, relationships between people, service time and comfort. One hundred people were randomly selected to take part in the study. The information collected was examined using simple linear regression analysis. The results of this study show that the magnitude of the relationship/correlation between patient satisfaction and the variable quality of health services at the Banjaran City Community Health Center is 75.5%. Community health centers are held to higher standards of service in an effort to improve the quality of healthcare in areas such as atmosphere, systems, human relations, waiting times, and comfort. Also anticipated are rapid and reliable patient satisfaction surveys.   Keywords : Community Health Center, Service Quality, Patient Satisfaction.